CO2 reforming of CH4 in single and double dielectric barrier discharge reactors: Comparison of discharge characteristics and product distribution. Issue 53 (November 2021) - Mei, Danhua; Duan, Gehui; Fu, Junhui; Liu, Shiyun; Zhou, Renwu; Zhou, Rusen; Fang, Zhi; Cullen, Patrick J.; Ostrikov, Kostya (Ken)
Highlights: CO2 reforming of CH4 was performed in DBDs with different dielectric layers. More intensified filamentary microdischarges were displayed in DBD-SD. DBD-SD exhibited higher reactant conversion and liquid product selectivity. Higher gas product selectivity and stable carbon balance were achieved in DBD-DD. Higher energy efficiency for plasma reforming process was obtained in DBD-SD. Abstract: CO2 reforming of CH4 in a non-thermal plasma process (e.g., dielectric barrier discharge, DBD) possesses dual benefits for our environment and energy needs. However, this process is strongly influenced by the dielectric structure of the DBD. Here, plasma CO2 reforming of CH4 has been performed in both single-dielectric and double-dielectric DBD (DBD-SD and DBD-DD) reactors under atmospheric pressure. Electrical and optical characterization, along with temperature measurements are performed to understand the influence of the DBD-SD and DBD-DD designs. Reactor performance for reforming is compared under different discharge powers. The results show that CO2 /CH4 discharges in both DBD-SD and DBD-DD display typical filamentary microdischarges. Compared with the DBD-DD, the DBD-SD reactor exhibits a larger number and higher intensity of current pulses, which leads to a higher electron density and formation of reactive species. The highest conversion of CO2 (24.1 %) and CH4 (49.2 %) are achieved in the DBD-SD at a high discharge power (75 W). Moreover, higher selectivities of gaseous products are obtained in the DBD-DD, while the DBD-SD reactor shows a higher selectivity for liquid products, mainly including methanol and acetic acid. The highest energy efficiencies for reactant conversion (0.34 mmol/kJ), gaseous and liquid production formation (0.26 mmol/kJ and 0.015 mmol/kJ) are achieved in the DBD-SD reactor at a low discharge power (22 W), resulting from the low energy loss to the environment. However, the carbon deposited on the inner electrode surface in the DBD-SD would have an adverse influence on the reactor's performance. Further research on the optimization of the DBD reactor to establish an efficient plasma-catalysis system is required for industrial applications.